I am not sure what function you want to take the derivative of but I can help with the formula you want verified. So I will do the second part.

We know that if sin^(-1)(x) = y then x = sin(y)

`tan(y) = sin(y)/cos(y) = sin(y)/(sqrt(1-sin^2(y)))`

Substituting x for sin(y) we get

`tan(y) = x/(sqrt(1-x^2))`

Taking the inverse tangent of both sides we get and noting that `tan^(-1)(tan(y)) = y`

`y = tan^(-1)(x/sqrt(1-x^2))` and since `y = sin^(-1)(x)` we have

`sin^(-1)(x) = tan^(-1)(x/sqrt(1-x^2))`

## We’ll help your grades soar

Start your 48-hour free trial and unlock all the summaries, Q&A, and analyses you need to get better grades now.

- 30,000+ book summaries
- 20% study tools discount
- Ad-free content
- PDF downloads
- 300,000+ answers
- 5-star customer support

Already a member? Log in here.

Are you a teacher? Sign up now